HISTORIOGRAPHY OF HADITH STUDY IN INDONESIA - Hara, Manahara Alamsyah Lubis; Fahrul Reza, Raja (Ushuluddin Faculty, PTIQ Institute, 2024)
Abstract This article describes the study of hadith in Indonesia within the scope of historical science. Telling the story of hadith studies in Indonesia cannot be separated from how Islam entered Indonesia and all phases of its development even though in its early history hadith studies did not receive more attention from Indonesian Muslims but in the end, hadith could develop rapidly and become a separate discipline. This article uses a qualitative method that focuses on data related to the history of the development of hadith studies in Indonesia sourced from books, journals, and scientific articles. The article shows that in the history of the development of hadith studies in Indonesia, it basically started since the beginning of Islam entering Indonesia, then continued to enter educational institutions until this century. Although there was a period when hadith studies stagnated due to the absence of works that appeared in that century. Keywords: Historiography, Hadith, Indonesia.